Efficient Hydraulic Flushing Gate System for Managing Sedimentation in Open Drain - Leong, Geok Teng (Universiti Malaysia Sarawak (UNIMAS), 2019)
The efficiency of hydraulic flushing gate system for managing sedimentation in open drain was evaluated in this study. The aims of this study include the investigation on the factors that influence sediment removal efficiency, identify the potential failure mode, effect and root cause in using hydraulic flushing, applying FMEA with FIS_RPN model and obtain FRPN on mechanical failure of hydraulic flushing gate system, and to establish a general guideline and management plan for active sedimentation control in open drain. Some experimental works were conducted and proven that number of flush, duration of flushing and sediment bed length are the important parameter in affecting sediment flushing efficiency. Besides that, field investigation shows that environment factor contribute to the failure mode of flush gate during on-site operation. FMEA results show that the size of hinge has the highest FRPN value of 269.4 which is the most critical component affecting the flush gate design. In addition, the gate holder has the highest FRPN value of 266.1 which mean to pay extra attention in the flush gate installation process. Overall, the risk associated with the current design to the flushing operation was considered moderate. In short, the experimental data provides a clear direction in designing the dimensions of flush gate and the selection of site in planning stage. The proposed techniques for the failure analysis will help to understand the failure behavior of the components during construction, installation and operation stage. A general design guideline and management were presented to provide better understanding and precaution on the use of flush gate system for open drain.